Belanja Pemerintah, FDI, Pertumbuhan Ekonomi, Pertumbuhan Industri, dan Kemiskinan di Indonesia - Najmi, Isthafan; Hasrina, Cut Delsie; Asmawati, Asmawati; Ansari, Rizal (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
In this new era of globalisation, all countries including Indonesia are targeting poverty alleviation to help people achieve welfare. Furthermore, this study empirically examines the impact of government spending, FDI, economic growth, and industrial growth on poverty. This research uses the Autoregressive Distributed Lag (ARDL) method. The data used is time series data from 1972 to 2021 obtained from the World Development Indicator website. The findings of the ARDL estimation show that government spending and industrial growth increase household income, both in the long-run and the short-run. In contrast, economic growth is negatively associated with poverty in both the short and long run. Meanwhile, FDI has no significant effect in the short term, but a significant negative effect in the long term, which has worsened poverty in Indonesia.